Impact of a pain education program for people with spinal cord injury who experience neuropathic pain - Cherup, Nicholas P.; Anderson, Kimberly D.; Wong, Marlon L.; Fernandez, Gabriel E.; Robayo, Linda E.; Roach, Kathryn; Vastano, Roberta; Widerstrom-Noga, Eva (Frontiers in Pain Research, 2025)
BackgroundNeuropathic pain is common after spinal cord injury (SCI). Despite the availability of various treatments, many report inadequate pain relief, and various side effects.ObjectiveThe primary purpose of the current study was to explore participants’ perspectives on a brief, four-week virtual pain education program and second to evaluate any effects on pain and psychosocial factors.MethodsThis study included 36 participants with SCI who experienced moderate to severe neuropathic pain and explored their perspectives on the pain program using qualitative interviews and evaluated a small set of self-reported pain outcomes.ResultsThe analysis and coding of the qualitative interview data resulted in two primary overarching themes: Benefits of pain education and Content and delivery of pain education. The Benefits of pain education theme was further analyzed and divided into 6 subthemes: Learning about pain and treatment options in general, Learning from and interacting with peers, Learning about non-pharmacological approaches and ways to self-manage pain, Learning about pathophysiology of pain, Learning about pain medication, and Improving communication about the lived experience with pain. Under the main theme of Content and delivery of Pain Education, there were three subthemes: Positive, No effect or negative, and Change suggestions. Specifically, participants reported having a better understanding about treatment options, how their peers managed their pain, and the underlying causes and types of pain. Participants also perceived that this knowledge would improve their ability to talk to others about their pain. Participants mentioned the topics discussed and the small group interactive settings as positive aspect of the education, although some did not benefit or felt that focusing on pain made pain more obvious to them. The overall benefit was consistent with small but significant improvements in perceived pain interference with daily activities and difficulty in dealing with pain (p < 0.05).ConclusionOverall, these findings suggest that a brief, virtually administered pain education program in a small group setting may be a positive addition to an interdisciplinary pain program. Future research should continue to develop and individually tailor such programs in this population, as these approaches are low-cost and easily accessible.